Kindlin-2 links mechano-environment to proline synthesis and tumor growth - Ling Guo (Nature Portfolio, 2019)
The mechano-properties of the Extracellular Matrix (ECM) are important for tumorigenesis. Here, the authors show that the stiffening of the ECM promotes translocation of the focal adhesion protein—Kindlin-2—to the mitochondria, where it interacts with the proline synthesis enzyme PYCR1, stimulating proline synthesis and cell proliferation.